(3GddBdF GdfXejI ef oeNJGQGJ GdjJjeIs - (3ENJjGQ YHO Gddg Hf YHO Gddg Hf SdGeI GdCOchj, GdeYQha HGdeDPfs
(3ChdgG (B:s
(3hHYO abO GeQfj GdCN aj Gddg JYGdi GdTjN YHO GdQMef GdHSjhfj Gf GNJUQ dg aj gPg GdChQGb ef cJGH jJjeI GdOgQ ddEeGe CHj efUhQ YHOGdedc ef eMeO GdKYGdHj s
(3BNQgG (B:s
(3haj GdCUd Gdefbhd efg HYOPcQg (B- (3Cj GHj GdaJM GdHSJj(B- (3PcQ GHj SdjeGf GdNWGHj , hgh ecJJH HgGeT GdcJGH , hHJQJjH eGHYOg ef GdJQGLe Je GdcJGH hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG GNJjGQGJ oCNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B352 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs